2015
DOI: 10.1007/s12031-015-0613-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Waterpipe Tobacco Smoke Exposure on Learning and Memory Functions in the Rat Model

Abstract: Tobacco smoking is a global health hazard that kills about 5 million people annually. Waterpipe smoking is among the most popular methods of tobacco consumption world-wide. In this study, we investigated whether waterpipe smoking impairs learning and memory in the hippocampus, a question of special concern due to the particular popularity of waterpipe use among youth. Additionally, possible molecular targets for expected learning and memory impairment were determined. In this study, rats were exposed to waterp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 69 publications
(95 reference statements)
2
17
0
Order By: Relevance
“…We found that C57BL/6J strain was more susceptible to acute WPS-induced oxidative stress response among the two strains. Our results are consistent with earlier findings that WPS induces oxidative stress by generation of ROS and depletion in GSH levels and increase in GSSG levels in several organs (Nemmar et al 2013;Ali et al 2017;Alzoubi et al 2015;Rababa'h et al 2016). It could also be possible due to the formation of GSH conjugates or rapid consumption of GSH during the breakdown of free radicals induced by WPS, thereby altering GSH redox system (Rahman and MacNee 1999).…”
Section: Discussionsupporting
confidence: 94%
“…We found that C57BL/6J strain was more susceptible to acute WPS-induced oxidative stress response among the two strains. Our results are consistent with earlier findings that WPS induces oxidative stress by generation of ROS and depletion in GSH levels and increase in GSSG levels in several organs (Nemmar et al 2013;Ali et al 2017;Alzoubi et al 2015;Rababa'h et al 2016). It could also be possible due to the formation of GSH conjugates or rapid consumption of GSH during the breakdown of free radicals induced by WPS, thereby altering GSH redox system (Rahman and MacNee 1999).…”
Section: Discussionsupporting
confidence: 94%
“…Since the activity of GPx has a direct impact on the ability of cells to defend against oxidative stress, recent studies have focused on examining the impact of drug abuse on GPx activity (Biala et al, 2017, Gong et al, 2017. Exposure to water pipe smoke, for instance, was found to reduce the activity of GPx in the HIP (Alzoubi et al, 2015). This study also found a significant impairment in the memory and learning of these male Wistar rats.…”
Section: Accepted Manuscript 19mentioning
confidence: 61%
“…Radial arm water maze (RAWM), which is available at the laboratory of Jordan University of Science and Technology was used to test spatial learning and memory as described previously [10][11][12]48]. …”
Section: 3behavioral Testmentioning
confidence: 99%